Pengembangan Rules-Driven Workflow Management System (RDWfMS) dengan Menggunakan Teknik Data Mining untuk Sistem Informasi Research Center - Shaufiah Shaufiah (School of Computing, Telkom University, 2017)
The tight competition of business and technology today makes the organisation must be able to adapt to changes. The changes could affect not only business process model of the organisation but also their information system, which lead to high cost and time-consuming. Therefore, the design and implementation of an information system should handle with care. Furthermore, the organisation also needs to process data into information and knowledge to support their business. Hence, this research is developed to undertake those problems by developing the information system using hybrid approach of the workflow system and data mining technique with research centre organisation as a case study. The system named as SIMPLER which applying rules-driven workflow and data mining to process data into information and knowledge from research data. SIMPLER tested by measuring its ability as a workflow management system as well as measuring the quality based on end-user satisfaction and perception by using WebQual. Based on the test results indicate that the SIMPLER been able to satisfy the need for business process execution XYZ research centre, able to adapt to changes without reconstructing the source code and gained end users satisfaction of 81.81% and 85% of accuracy.